Formulation of new drug delivery systems for insulin from natural bioactive biocompatible polymers - Howida A. Fetouh; Engy E. A. Aleem; Najiyah H. Mohammed; Jihad M. Abd-Almajeed Aldesouky; Amel M. Ismail (Scientific Reports)
Abstract New insulin drug delivery systems (IDDs): insulin@chitin; insulin@chitin-grafted (g)-guar gum were prepared by using a modified sol–gel method. Insulin vials were loaded on the safe natural inert bioactive polymers (chitin and chitin-g-GG copolymer) carriers using water green solvent. Traces amount additives were below toxicity limits. Guar gum increased the numbers of the functional groups of the polymer carrier. Insulin release monitored at 37 ± 0.5 °C and buffer solutions of pH (1.2, 6.8 and 7.4) simulating physiological body fluids: stomach, intestine colon and blood stream. Insulin released from insulin@chitin only at pH 7.4. No release observed at pH 1.2, 6.8 due strong bonding to acetyl group of chitin. Insulin@chitin-GG system showed sustained targeting insulin-release at pH: 6.8 > 7.4 > 1.2. Release data obeyed pseudo second order kinetic model indicating that IDDs is heterogeneous solid surface of energetically different active sites. Each insulin molecule occupied two active sites. The slow release at pH 1.2 indicated protection against stomach juice. Release kinetic depend on physicochemical characteristics (porosity, swelling ratio as well as peptide and amino acid sequence). Both IDDs showed negative zeta potential indicating stability against aggregation. Gaur gum improved particle size distribution and insulin release.